Fuzzy-PI based automatic generation control of two-area interconnected nonlinear power system. (2017) - Prasad, Lal Bahadur; Tyagi, Barjeev; Gupta, Hari Om
This paper presents the modelling, simulation and performance analysis of automatic generation control (AGC) of two-area interconnected nonlinear power system using fuzzy logic system. Fuzzy control, one of the intelligent control techniques, uses the human expert knowledge to make control decisions. Mamdani fuzzy inference system has been used to tune proportional-integral controller for AGC of two-area interconnected nonlinear power system. To compare the results the conventional integral control is also presented. The simulation of control schemes has been carried by developing MATLAB-SIMULINK models. The simulation results and analysis justify the comparative advantages of fuzzy control method.